Effect of process parameters on the impact strength of fused filament fabricated (FFF) polylactic acid (PLA) parts. (2021) - Bardiya, Shrikant; Jerald, J.; Satheeshkumar, V.
Abstract: Fused Filament Fabrication (FFF) is a well-known additive manufacturing (AM) process that is widely used in developing models, prototypes and functional parts for numerous industrial applications because of its potential for creating parts with sophisticated design in the stipulated time along with less wastage of material. Selecting input variables in FFF is a difficult task as they directly affect the performance of the specimens. In this experimental investigation, efforts are made to identify the influence of three process parameters on the impact strength of parts produced by FFF. The three important process parameters selected in this study are layer thickness, build orientation, and infill density. Three levels of each parameter is selected and Taguchi L9 orthogonal array is made. The build material used to make all the specimens is polylactic acid (PLA). All the test specimens for impact strength are made according to ASTM D256 standard, which is used for izod impact test. Additionally, the effect of process parameters on the manufacturing time of impact test samples is also presented in this study.